The Influence of Organizational Culture on Cooperation Apparatus at the Baringg Village Office, Lilirilau District, Soppeng Regency - Burhanuddin Burhanuddin; Erna Erna; Asmanurhidayani Asmanurhidayani; Sofyan Marzuki; Eka Patmasari; Alda Faradillah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Each agency is formed with a specific purpose to be realized. The achievement of these goals is greatly influenced by the behavior, attitudes, and contributions of individuals in the organization. The success of an agency in realizing its goals depends on the ability of employees to carry out their functions and manage each work unit effectively. This is because the achievement of organizational goals is basically the result of the efforts, cooperation, and active role of all elements involved in the agency. The purpose of this study is to analyze the influence of organizational culture on the cooperation of the apparatus at the Baringg Village Office, Lilirilau District, Soppeng Regency. The research applied a quantitative approach with the census research type. The data analysis techniques applied include the analysis of correlation coefficients, determination coefficients, and simple linear regression, while data collection techniques are carried out by observation, documentation, and the distribution of questionnaires that are tailored to the needs of the research. The results of the study illustrate that the organizational culture and cooperation of the apparatus at the Baringeng Village Office are in the very good category. In addition, organizational culture has been proven to have a positive influence on the cooperation of apparatus with a very strong level of relationship. The magnitude of the influence exerted reached 76.1%, while the remaining 23.9% was influenced by other factors outside the variables studied in this study.